METABOLIZABLE ENERGY AND CRUDE PROTEIN REQUIREMENTS OF TWO QUAIL SPECIES (Coturnix japonica and Coturnix ypsilophorus) - R. Jahanian; M. A. Edriss (Journal of Animal and Plant Sciences, 2015)
The present study aimed to investigate the effects of different levels of dietary metabolizable energy (ME) and crude protein (CP) on performance and carcass characteristics of Japanese (Coturnix japonica) and Brown (Coturnix ypsilophorus) quails during a 42 d feeding trial. A total of 720 (360 per each species) one week-old quail chicks were randomly (by species) distributed between 72 cages according to a 3 × 3 × 2 factorial arrangement of treatments (3 dietary ME levels: 2800, 2900 and 3000 kcal/kg of diet; 3 different CP levels: 22, 24 and 26%; and 2 quail species: Japanese and Brown) with 4 replicates of 10 birds each. Performance parameters were recorded biweekly. Results showed that except 22-35 d period, average daily feed intake (ADFI) was affected (P<0.01) by dietary ME level with the lowest ADFI assigned to those fed diets containing 3000 kcal ME/kg. Japanese quails consumed (P<0.01) more feed than Brown quails during 22-35 and 36-49 d of age. Increase in dietary ME and CP levels to 2900 kcal/kg and 26%, respectively, increased (P<0.01) average daily weight gain (ADWG), and Japanese quails had the greater ADWG compared with Brown quails. Feed conversion ratio (FCR) was improved by incremental levels of dietary ME (P<0.01) and CP (P<0.05) throughout the trial period. Japanese quails showed the better (P<0.01) FCR values compared with Brown quails during 22-49 d of age. Increase in dietary ME and CP levels increased (P<0.01) carcass and breast yields. Highly positive correlations were found among daily ME/CP intakes and ADWG, ADFI, and carcass yield. The present findings indicate that Japanese quails need the diets containing 3000 kcal ME/kg and 26% CP during the first weeks of age to achieve optimum growth performance. Dietary CP level can be reduced to 24% CP at the older ages. The nutritional demands of Brown quails were determined to be 2900 kcal ME/kg and 24% CP during the starter period and 2900 kcal/kg ME and 22% CP at the remaining growth period.
Keywords: Quail; Coturnix japonica; Coturnix ypsilophorus; Dietary protein requirements; Metabolizable energy; Performance; Carcass characteristics